A pilot training program for point-of-care ultrasound in Kenya - Greg Bell (African Journal of Emergency Medicine, 2016)
Ultrasound is an effective and affordable clinical diagnostic tool highly attractive for use in low and middle income countries (LMICs), but access to training programs in these countries is limited. The objective of our study was to develop and pilot a program for healthcare providers in Kenya in the use of point-of-care ultrasound. Methods: Trainees were recruited in district hospitals for participation in three all-day workshops held every 3–5 months from September 2013 through November 2014. Prior to the initial workshop, trainees were asked to study a training manual, and a knowledge test was administered. Ultrasound-credentialed emergency physicians provided brief didactic lessons then hands-on training for eFAST and obstetric training. This was followed by an observed assessment of scanning image quality (IM) and diagnostic interpretation (IN). Results: Eighty-one trainees enrolled in four initial training sessions and 30 attended at least one refresher session. Among those trainees who attended refresher sessions, there was an increase in the proportion passing both the knowledge and practical tests at the follow-up, as compared to the initial session. Overall, mean practical skill scores also trended toward an increase over time, with a significantly higher mean score in November 2014 (2.64 + 0.38, p = 0.02) as compared to March 2014 (2.26 + 0.54), p < 0.05. Pre-workshop preparation evolved over time with the goal of maximizing trainee readiness for the hands-on course. A strong correlation was observed between knowledge and practical skill scores illustrating the importance of pre-workshop training. Conclusions: Our pilot workshop showed promise in promoting knowledge and practical skills among participants, as well as increasing use in patient care. Results also suggest that refresher training may provide additional benefits for some participants. These findings provide a strong rationale for expanding the training program and for measuring its clinical impact.